Investigation of potential relationship betweenmazEF3, relJK, and vapBC3 genes and antimicrobial resistance inMycobacterium bovis - Maryam Shafipour; Abdolmajid Mohammadzadeh; Ezzat Allah Ghaemi; Pezhman Mahmoodi; Nader Mosavari (BMC Infectious Diseases)
Abstract Background Small genetic modules, such as toxin-antitoxin (TA) systems, play specific roles in persistence, antibiotic resistance, and virulence in pathogenic bacteria. Given the transmission of M. bovis to humans and the importance of the spread of antibiotic resistance in this bacterium, this study aimed to compare the presence and sequences of the mazEF3, vapBC3, and relJK genes in type II TA systems of both resistant and sensitive M. bovis isolates. Methods Fifty-nine M. bovis isolates were obtained from the Razi Vaccine and Serum Research Institute in Iran. M. bovis isolates were confirmed using GeneXpert MTB/RIF and by evaluating of the pncA gene. Rifampin- and isoniazid-resistant isolates were identified using Multiplex Allele-Specific Polymerase Chain Reaction (MAS-PCR). The presence and mutations of the mazEF3, relJK, and vapBC3 genes were analyzed by PCR sequencing. Molecular docking was performed to predict the binding affinity of RelJ to RelK. Results Of the 59 M. bovis isolates, 13 (22%) and 3 (5.1%) were resistant to rifampin and isoniazid, respectively. The most common mutations in the rifampin-resistant isolates were observed at codons rpoB516 (92.3%) and rpoB531 (84.6%). The nucleotide sequences of mazEF3, vapBC3, and relK were identical to those in the reference strain in all cases. Molecular docking analysis suggests that the mutant RelJ shows improved binding affinity in comparison to the non-mutant protein for the RelK toxin. Conclusions These findings suggest that the relJ gene may be associated with antibiotic resistance in M. bovis. Therefore, increasing the sample size is recommended for a more in-depth investigation of relJ. If successful, this biomarker could be utilized for developing new methods to identify resistant isolates.